Kaffārah Rules on Having Intercourse During Ramaḍān: Gender Analysis of Imam Nawāwī and Ibn Qudāmah’s Opinions - Billah, Mu'tashim; Nurdiansyah, Rifqi; Alyaparangu, Kaukabilla (UIN Sunan Kalijaga Yogyakarta, 2021)
This article tries to analyze the doctrine of kaffārah as the repentance for those who break the fast doing an intercourse in the day of Ramaḍān based on the opinions of Imam Nawāwī and Ibn Qudamah viewed from the perspective of gender. This is a library research that used descriptive-comparative methods along with normative and gender equity approach that discusses the text and modern context. The data was derived from the fikih’s books. This article shows that Muslims who commit a sexual intercourse in the day of Ramaḍān are burdened by an expiation that is mentioned in ḥadīṡ. Imam Nawawi stated that wife is not burdened by an expiation if she commits the intercourse, either by her willingness or under the compulsion. While Ibn Qudāmah stated that wife is burdened by an expiation if she commits it by her willingness and the legal burden will be lost if she is being under compulsion. From the perspective of gender, there is no difference between both man and woman’s kaffārah obligation. Both will get the consequence from all they have done, because both are the subjects of law. They should discuss each other on what choices to expiate their sins.